Rationality of insurance firms' forecasts: Results of unbiasedness and efficiency tests - Habibullah, Muzafar Shah
Many applied studies have tried to test the implications of rational expectations hypothesis on survey data. This study provides evidence on the rationality of economic forecasts made by insurance firms in a developing economy-Malaysia. Our unbiasedness test results suggest than anticipated gross revenue and employment are unbiased predictors of actual gross revenue and employment respectively. Furthermore, our efficiency tests results indicate that insurance firms utilized relevent information efficiently at the time the forecasts were made.